SFG in the Students’ Interpretation of Song Lyrics - Yeni Dewi Cahyani (Journal of English Language Learning, 2017)
ABSTRACT Song lyrics can give important clues about what people thought and felt, their daily struggles, and their dreams about the future.The language of the lyrics itself can express different meaning. It can be also said that song always sends message in every lyrics; and every song has the lyrics which gives a different meaning according to the language use. The problem is that the literal meaning of song lyrics is often hard to establish, and this meaning is usually enriched with allusion, suggestion, and implied meanings. One of the best ways to get an idea of the different things that a song means and has meant is to see what people have said about it. The purpose of this study is to apply the SFG in interpreting the student’s interpretation of song lyrics and the meaning making through representational strategies. The data were gathered from the students’ interpretation of song lyrics through writing task.The theme song used here is focused on the songs about relationships i.e., “Rolling in the deep” (Adele) and “Because of you” (Kelly Clarkson).The instrument to be used in analyzing the data is a systemic functional grammar (SFG). Having analyzed the students’ texts using transitivity, the study shows that there are different types of processes and their ways applied in the texts. The finding shows that the differences occur in the use of processes and their functions. Construction of interpretation in this case depends on clues from the text and probability, which is determined both by facts from texts and connotations. In relation to the meaning making through representational strategies, the different types of processes dominated in the students’ text synergized to build the representation of the song meaning related to the meaning which was meant by the song writer.Key words: SFG, interpretation, representation, song lyrics.